Production Performance, Phenotypic and Carcass Quality Sensory Evaluation of Kadaknath, Rhode Island Red Chicken and their Reciprocal Crosses - Bhagora, Nikesh J.; Mishra, Ramkailash; Savaliya, Fulabhai P.; Patel, Atul B.; Lonkar , Vijay Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The performance of reciprocal crosses of Rhode Island red (RIR) and Kadaknath was studied for comparison with the performance of purebred RIR and Kadaknath. A total of 292 birds comprising of purebred RIR and Kadaknath and reciprocal crosses were divided into four groups, viz., 74 birds of purebred Rhode Island red (R), 70 birds of purebred Kadaknath (K); and 72 birds of Rhode Island Red x Kadaknath (R x K) and 76 birds of Kadaknath x Rhode Island Red (K x R) as reciprocal crosses. The body weight (BW) at day-old, 4, 8, 12, 16, 20, 28, 36, and 40 weeks of age, age at first egg (AFE) and total egg number (TEN) up to 40th week of age were recorded for each group. The phenotypic characteristics of birds and their egg quality parameters were recorded at the 40th week of age. The phenotypic and carcass qualities were recorded at the 28th week of age for male and female birds. The results of the study indicated that the body weight (BW), egg weight (EW), TEN, and dressed weight (DW) for purebred RIR were significantly (p <0.05) higher than purebred Kadaknath. The EW of both the reciprocal crosses was significantly (p <0.05) higher than the purebred Kadaknath. Use of RIR female in a cross with Kadaknath males significantly (p <0.05) increased TEN and BW. The use of RIR male in crosses with purebred Kadaknath female resulted in higher DW for their crossbred male. Use of either male or female purebred RIR in crosses with Kadaknath did not affect crossbred female DW. Red-breasted black plumage, white skin, and mixed-colored ear lobe were observed in R x K crosses. Silver laced black breast, black plumage color, black colored skin, and black ear lobes were observed in K x R crosses. The results of the study indicated that reciprocal crossing between RIR and Kadaknath breeds improved egg shape index (SI), albumen index (AI), yolk weight (YW), albumen weight (AW), shell weight (SW), shell thickness (ST). The overall acceptance of crossbred birds’ meat was higher when RIR female was used in a cross with Kadaknath. It was concluded that using K x R cross would help improve the production performance, egg quality, and consumer demand for rural and backyard poultry farming in India.